2018
DOI: 10.14569/ijacsa.2018.091115
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Technique for Tunneling Mechanism of IPv6 using Teredo and 6RD to Enhance the Network Performance

Abstract: Internet Protocol version 4 (IPv4) addresses have been depleted. Many Internet Service Providers (ISPs), researchers and end users are migrating from IPv4 to IPv6 due to strong features of IPv6 and limitation in IPv4. Different tunneling techniques have been deployed to migrate on IPv6 for ordinary users. However, these techniques create many issues such as compatibility, complexity, connectivity and traffic. Due to the dissimilar header structure and incompatibility of IPv4 and IPv6, the devices are unable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The jumbo frames were transmitted through the tunnel, and it was found that the performance of the hybrid technique had better results than an individual one. The hybrid technique had a better packet delivery ratio of 98% and a minimum delay for the extensive frame network [49]. In 2018, K. El Khadiri et al build and simulated dual-stack, manual, and automatic 6to4 tunnel for real-time video conferencing applications using RIP, OSPF, and IS-IS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The jumbo frames were transmitted through the tunnel, and it was found that the performance of the hybrid technique had better results than an individual one. The hybrid technique had a better packet delivery ratio of 98% and a minimum delay for the extensive frame network [49]. In 2018, K. El Khadiri et al build and simulated dual-stack, manual, and automatic 6to4 tunnel for real-time video conferencing applications using RIP, OSPF, and IS-IS.…”
Section: Literature Reviewmentioning
confidence: 99%